Fabrication of Low-Roughness Au/Ti/ SiO2/Si Substrates for Nanopatterning of 16-Mercapto Hexadecanoic Acid (MHA) by Dip-Pen-Nanolithography - A. Kumar; P.B. Agarwal; S.K. Gupta; A.K. Sharma; D. Kumar; Chandra Shekhar (Журнал нано- та електронної фізики)
Silicon based low-roughness Au/Ti/SiO2/Si substrates were fabricated using standard IC fabrication processes. Evolution of surface roughness during substrate fabrication process was studied. Fabrication process steps, namely, thermal oxidation and e-beam evaporation for ultra-thin Ti(~ 5 nm)/Au(22 nm) films, were optimized to result in surface r.m.s roughness ~ 0.2 m and ~ 1.0 nm, after thermal oxidation and Ti/Au deposition steps respectively. Surface roughness was estimated by atomic force microscope (AFM) imaging and image analysis. Nano-patterning experiments using thiol based 16-MHA molecular-ink on fabricated substrates were carried out, under controlled environment conditions, by dip-pen-nanolitho-graphy (DPN) technique. Minimum line-width ~ 60 nm and circular dots radius ~ 175 nm were patterned.